(untitled) (Journal of Engineering, 2015)
Buildings such as malls, offices, airports and hospitals nowadays have become very complicated which increases the need for a solution that helps people to find their locations in these buildings. GPS or cell signals are commonly used for positioning in an outdoor environment and are not accurate in indoor environment. Smartphones are becoming a common presence in our daily life, also the existing infrastructure, the Wi-Fi access points, which is commonly available in most buildings, has motivated this work to build hybrid mechanism that combines the APs fingerprint together with smartphone barometer sensor readings, to accurately determine the user position inside building floor relative to well-known landmarks in the floor. Also the proposed system offers a monitoring activity which lets the administrator to watch and locate certain user inside the building.The system is tested in a big building indoor environment and achieved positioning accuracies of approximately 2.1 meters.